Learning to Solve Class-Inclusion Problems: The Roles of Quantification and Recognition of Contradiction. - Judd, Susan A.; Mervie, Carolyn B. (Child Development, 1979)
The present experiment was designed to examine the roles of quantification and awareness of contradiction in children's class-inclusion reasoning. 5-year-olds were presented with class-inclusion problems and were required to count the superordinate and the two subordinate classes before answering the standard class-inclusion question. It was made clear to some of the children, through a counting-questioning procedure, that their counting of the relevant classes and their answers to the inclusion questions were contradictory. Children who counted the relevant classes but were not made aware of the contradiction between their counting and their answers performed as poorly on the class-inclusion problems as a group of control children who did not count. Children who received contradiction training solved the class-inclusion problems significantly better than children who did not. These children were also able to solve class-inclusion problems without assistance during both an immediate and a delayed posttest. Successful solution of the posttest problems could not be attributed to learning a rule about which quantity is always correct.